EKSPLORASI GAYA BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS NIAS DALAM MENYELESAIKAN TUGAS BERBASIS PROYEK - Sadiana Lase (Universitas Islam Sumatera Utara, 2025)
This study aims to explore the learning styles of Mathematics Education students of the Faculty of Teacher Training and Education, Nias University in completing project-based assignments. The background of this study is based on the fact that each student has a different learning style tendency, which has a direct impact on the strategy and results of completing assignments. This study uses a qualitative approach with a case study method. The subjects of the study consisted of seven active students who were selected purposively based on their involvement in lecture project assignments. Data collection techniques include in-depth interviews, observation, and documentation. The results of the study indicate that students have a tendency towards three main learning styles, namely visual, auditory, and kinesthetic. Students with a visual style prefer the presentation of information graphically and systematically. Auditory students tend to understand the material through discussion and verbal explanation, while kinesthetic students are more active in assignments that involve direct practice. These variations in learning styles affect the way students plan, work on, and complete project assignments. It was also found that group work is more effective when each member has a complementary learning style. This study concludes that understanding students' learning styles is important for lecturers to consider in designing project-based assignments. With the right approach, the learning process will be more inclusive and meaningful for each individual.